2019
DOI: 10.1016/j.jbiomech.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Virtual structural analysis of tibial fracture healing from low-dose clinical CT scans

Abstract: Quantitative assessment of bone fracture healing remains a significant challenge in orthopaedic trauma research. Accordingly, we developed a new technique for assessing bone healing using virtual mechano-structural analysis of computed tomography (CT) scans. CT scans from 19 fractured human tibiae at 12 weeks after surgery were segmented and prepared for finite element analysis (FEA). Boundary conditions were applied to the models to simulate a torsion test that is commonly used to access the structural integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
(23 reference statements)
0
24
0
Order By: Relevance
“…For example, we recently developed CT-derived computational methods to calculate the virtual torsional rigidity (VTR) of human tibial fractures after 12 weeks of healing. 9 In a pilot study, we showed that this measure is strongly correlated with clinical healing outcomes, such as time to clinical union. 10 Furthermore, integrating image-based models in preclinical in vivo studies may reduce the required number of experimental animals, in accordance with three R principles, by allowing noninvasive follow-up assessments of structural healing kinetics.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, we recently developed CT-derived computational methods to calculate the virtual torsional rigidity (VTR) of human tibial fractures after 12 weeks of healing. 9 In a pilot study, we showed that this measure is strongly correlated with clinical healing outcomes, such as time to clinical union. 10 Furthermore, integrating image-based models in preclinical in vivo studies may reduce the required number of experimental animals, in accordance with three R principles, by allowing noninvasive follow-up assessments of structural healing kinetics.…”
Section: Introductionmentioning
confidence: 87%
“…[1][2][3][4][5][6][7][8] This technique is able to accurately capture both the complex geometries and localized material acquired by the CT scan to build representative animalspecific or patient-specific models. 9,10 FEA can then be used to simulate different loading scenarios and assess the structural biomechanics of the anatomy of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The process has been documented in extensive detail elsewhere. 18 The strict workflow control produces data that is highly repeatable and any two individuals following the proscribed process would produce nearly identical summary measures. This study also suggests some potential difficulties with the widely used RUST score.…”
Section: Discussionmentioning
confidence: 99%
“…The complete workflow for generating the injured and intact models is summarized in Figure 1 and discussed in detail elsewhere. 18 A virtual torsion test was chosen as the summary measure of mechanical integrity in each model. Torsional stiffness relative to intact paired controls is often used as a summary indicator of healing in preclinical models, [19][20][21][22][23] because it is direction independent.…”
Section: Ct Scan Processing and Injured Limb Reconstructionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] This technique is able to accurately capture both the complex geometries and localized material acquired by the CT scan to build representative animal-specific or patient-specific models. 9,10 FEA can then be used to simulate different loading scenarios and assess the structural biomechanics of the anatomy of interest.…”
Section: Introductionmentioning
confidence: 99%